Replicating a study about children’s drawings concerning radiation - T. Plotz; F. Hollenthoner (Multidisciplinary Journal for Education, Social and Technological Sciences, 2019)
Radiation surrounds us in various forms and plays a huge role in our everyday life. However, little is known about student and children’s conceptions of this topic. This study is part continuation part replication of the studies carried out by Neumann and Hopf (2013). The method employed in both studies was identical. 459 students drew pictures associated with the concept “radiation” under observation. The resulting motives were subsequently categorized and compared. In this study the children barely associate the concept of “radiation” with the Fukushima Nuclear Disaster. Moreover, a number of differences could be realized when compared to the reference study. For instance, significantly more students drew cell phones and computer monitors in the current study. Additionally, a greater number of drawings related to radioactivity could be observed. Overall, the findings of this work indicate that not only are students exposed to the media at a much younger age, but also more frequently. This leads to the conclusion that more and more children build their own understanding of a particular subject, which could potentially result in misconceptions.